Comportamiento agronómico de variedades de frutilla (Fragaria x ananassa Duch.) de día corto y neutro en clima subtropical (Journal on studies and research of academic knowledge, 2022)
Strawberry cultivation is highly influenced by climatic factors such as temperature and particularly the photoperiod in short-day varieties. These conditions are those that limit a short period of production and also affect the productive potential. In order to evaluate the behavior of 7 varieties of strawberry in the southern region of Paraguay (6 varieties short-day and a neutral day variety) the variety comparison test is carried out between the months of March to August 2020. The transplant yield was 100%. A difference of more than 20 days was obtained at the beginning of the harvest, determining the most suitable Florida and Festival varieties for obtaining scoop fruits. The highest values obtained, regarding number of fruits per plant, fruit size and yield: total, commercial fresh fruit and non-commercial corresponded to the Sweet Charlie variety.
Keywords: Strawberry; Varieties; Subtropical